Letter from W. E. Muir to James Curtis Booth, March 11, 1856 - Muir, W. E. (1856)
Requisition for a shipment of alloyed metals from the Office of Supervising Inspector, Fourth District, New Orleans.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Alloys